Acute bronchodilator responses to β2-agonist and anticholinergic agent in COPD: Their different associations with exacerbation. (June 2017) - Konno, Satoshi; Makita, Hironi; Suzuki, Masaru; Shimizu, Kaoruko; Kimura, Hirokazu; Kimura, Hiroki; Nishimura, Masaharu; ,
Abstract: Background: Acute bronchodilator response (BDR) is a potential phenotypic characteristic of COPD. However, the clinical factors associated with BDR in patients with COPD remain unclear, particularly for BDR to anticholinergic agents. Objectives: We aimed to clarify the clinical factors associated with BDR to β2-agonist and/or anticholinergic agent, considering time-associated variations of BDR. We also evaluated the association between BDR and clinical course of COPD. Methods: We analyzed 152 subjects who participated in the Hokkaido COPD cohort study. We repeatedly measured BDR to salbutamol (400 μg) or oxitropium (400 μg) three times for each every 6 months alternately over 3 years. Reversibility was defined by ≥ 12% and ≥200 mL increase in FEV1 over baseline. All subjects were classified into three groups based on the BDR stability; consistently reversible, consistently irreversible, and inconsistent. We compared baseline clinical characteristics and the 5-year clinical course of COPD among the three groups. Results: For either agent, the mean blood eosinophil count was significantly higher in those with consistently reversible than those with consistently irreversible (p < 0.05). The subjects with consistently reversible to oxitropium (p < 0.05), but not to salbutamol (p = 0.56), showed increased risk of exacerbation compared with the other two groups. Conclusion: We identified the distinct clinical characteristics of COPD associated with acute BDR status. Increased cholinergic airway tone, which is reflected in the higher BDR only to anticholinergic agent, but not to β2-agonist, may be associated with exacerbation in COPD. Highlights: We clarified the clinical factors associated with acute bronchodilator response (BDR) to β2-agonist and/or anticholinergic agent. Blood eosinophilic count is a determinant of BDRs to both β2-agonist and anticholinergic agent. The consistently reversible BDR to anticholinergic agent, but not to β2-agnoist is associated with exacerbation risk in COPD. Increased cholinergic airway tone may be associated with exacerbation in COPD. Abstract : BDR to both β2-agonist and anticholinergic agent were associated with blood eosinophil count. Whereas, BDR to anticholinergic agent, but not to β2-agonist, was associated with exacerbation of COPD.